Dual-feasible functions for integer programming and combinatorial optimization : basics, extensions and applications /: basics, extensions and applications. (2016) - Alves, Cláudio; Clautiaux, Francois; Carvalho, José Valério de; Rietz, Jürgen
No abstract available